2012
DOI: 10.1002/jsfa.5723
|View full text |Cite
|
Sign up to set email alerts
|

Protein isolation from blue mussels (Mytilus edulis) using an acid and alkaline solubilisation technique—process characteristics and functionality of the isolates

Abstract: The pH shift method can be successfully used to extract functional proteins from mussels and add value to blue mussels unsuitable for human consumption (with or without shells).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…The results found in this study were in agreement with the previous findings reported by Tian et al . and Vareltzis and Undeland during the studies on common carp and blue mussel proteins.…”
Section: Resultssupporting
confidence: 94%
“…The results found in this study were in agreement with the previous findings reported by Tian et al . and Vareltzis and Undeland during the studies on common carp and blue mussel proteins.…”
Section: Resultssupporting
confidence: 94%
“…This is because more water allows for better solubility (Stefansson and Hultin 1994) and also creates a more diluted system, which causes less solubilized proteins to be retained in the pellet (Vareltzis and Undeland 2012). A higher proportion of water will also lower the ionic strength of the system, which could either increase or decrease protein solubility, depending on the shape of the salting-in/salting-out curve.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure, which often goes under the name ‘pH shift method,’ has also been applied, e.g. to shellfish (Vareltzis and Undeland 2012) and recently to microalgae (Cavonius et al 2015, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The latter (Veide Vilg and Undeland 2017) was, however, achieved when using a lower water to biomass ratio of 5.56:1(v/w) than the one used here 6:1 (v/w). It has clearly been shown how the addition of more water to the biomass (increased ratio of water/biomass) improves yield (Vareltzis andUndeland 2012, Veide Vilg andUndeland 2017) since the solubility of proteins is facilitated, and since the fractions removed during the pH-shift process become less concentrated. Also, Veide Vilg and Undeland (2017) did not apply a freeze-thawing step during the protein precipitation, the latter which was shown in this work to enhance precipitation for P. umbilicalis, U. lactuca, and S. latissima by 8, 4, and 14 percentage points, respectively.…”
Section: Protein Yield As a Function Of Extraction Methods And Speciesmentioning
confidence: 99%